3(u-2)-2=-6(-3u+4)-9u

Since u is on the right side of the equation, switch the sides so it is on the left side of the equation.

-6(-3u+4)-9u=3(u-2)-2

Simplify each term.

Apply the distributive property.

-6(-3u)-6⋅4-9u=3(u-2)-2

Multiply -3 by -6.

18u-6⋅4-9u=3(u-2)-2

Multiply -6 by 4.

18u-24-9u=3(u-2)-2

18u-24-9u=3(u-2)-2

Subtract 9u from 18u.

9u-24=3(u-2)-2

9u-24=3(u-2)-2

Simplify each term.

Apply the distributive property.

9u-24=3u+3⋅-2-2

Multiply 3 by -2.

9u-24=3u-6-2

9u-24=3u-6-2

Subtract 2 from -6.

9u-24=3u-8

9u-24=3u-8

Subtract 3u from both sides of the equation.

9u-24-3u=-8

Subtract 3u from 9u.

6u-24=-8

6u-24=-8

Add 24 to both sides of the equation.

6u=-8+24

Add -8 and 24.

6u=16

6u=16

Divide each term in 6u=16 by 6.

6u6=166

Cancel the common factor of 6.

Cancel the common factor.

6u6=166

Divide u by 1.

u=166

u=166

Cancel the common factor of 16 and 6.

Factor 2 out of 16.

u=2(8)6

Cancel the common factors.

Factor 2 out of 6.

u=2⋅82⋅3

Cancel the common factor.

u=2⋅82⋅3

Rewrite the expression.

u=83

u=83

u=83

u=83

The result can be shown in multiple forms.

Exact Form:

u=83

Decimal Form:

u=2.6‾

Mixed Number Form:

u=223

Solve for u 3(u-2)-2=-6(-3u+4)-9u